Reflective practice for professional development - Thompson, Carol (Routledge, 2022)
"Reflective Practice for Professional Development provides an accessible introduction to the theory and practice of reflection. In ten concise chapters it explores how reflecting on experiences can be used for professional development and help progress knowledge and skills. Using scenarios, questions and stories, the reader is encouraged to apply the content to their own context, demonstrating the importance of reflection in helping us to make sense as well as make the most of our professional experience. Exploring key themes such as the importance of criticality, models of reflection and connections between thought, language, and actions, it considers the ways in which reflection can widen perspectives, generate deeper understanding of professional challenges, and enhance creativity. Full of practical tools and approaches for enriching and recording reflections, this insightful book aims to simplify reflective practice for teachers. It is an ideal guide for anyone who needs to build reflection into their practice or their studies"--
Introduction -- Why should we reflect? -- Learning through practice -- Models of reflection -- The importance of critical thinking -- Diffusing the dynamite -- Tools for reflection -- Reflection for creativity -- Joining up the dots -- Reflecting with others -- Turning reflection into action -- Final thoughts -- Appendix.
Keywords: Reflective learning; Reflective teaching; Teachers; Career development